Pendidikan Anak dalam Perspektif Al-Qur’an Al-Karim : (Tinjauan QS. Al-Baqarah/2: 83 Dalam Tafsir Taisir Kariim Ar-Rahman fi Tafsir Kalam Al-Mannan) - Muhamad Abid Hadlori; Saeed Abdullah Saeed Saket; Sidiq Samsi Tsauri (ZAD Al-Mufassirin, 2020)
This research is aimed at collecting explanations of Qur'anic verses related to education of children through a literature study approach. With the scope of research based on explanations from the book Tafsīr Taisir Karīm Ar-Rahman fī Tafsīr Kalam Al-Mannan, especially explanations related to education of children. This research is aimed at restoring the educational vision of Muslims back to the guidance of the Qur'an and Al-Sunnah which is proven to be able to create an advanced and strong Islamic civilization by practicing the guidance of the Qur'an and Al-Sunnah and applying them in their lives so as to create a strong generation, tauhid, and noble character.